PRIM: a model case of collaborative governance - Agusdin Agusdin (Iapa Proceedings Conference, 2018)
That which looks like a road to Directorate General of Highways is a lifeline to citizens, a framework for development for regional government, and a source of livelihood in road construction. These four different perspective of stakeholders form the basis of innovative collaboration in the acclaimed Provincial Road Improvement Program (PRIM) in NTB. Quality of regional roads and road maintenance has vastly improved through the program, and its success lies in collaboration. This paper presents the four perspectives of the collaboration and concludes with lessons learnt. Representatives of each will be present at the IAPA conference presentation. (1) Local government of West Lombok will report how PRIM has resulted, in more productive investment in roads, and also how civil society engagement adds value and how managerial support improves regional government capacity. Local government will also indicate how the grant mechanism, hibah jalan, provides a valuable incentive to improve design and construction quality. (2) A representative of the Forum Lalu Lintas dan Angkutan Jalan, will describe the social inclusion aspects of PRIM, and how the outcomes satisfy real community needs. (3) A representative of the local engineering profession will demonstrate how PRIM enables them to be more professional and how it helps construction companies to gain a better business reputation. (4) The Head of Bina Marga’s subdirectorate for facilitating regional roads describes how observing the excellence of PRIM has led to plans to adopt PRIM practices nation-wide.